Deoxygenative Functionalizations of Aldehydes, Ketones and Carboxylic Acids - Li, Jianbin; Huang, Chia‐Yu; Li, Chao‐Jun (Angewandte Chemie International Edition, 2022)
The simple and efficient conversion of carbonyl compounds into functionalized alkanes via deoxygenation is highly enabling in chemical synthesis. This Review covers the recent methodology development in carbonyl and carboxyl deoxygenative functionalizations, highlighting some representative and significant contributions in this field. These advances are categorized based on the reactivity patterns of some oxygenated feedstock compounds, including aldehydes, ketones and carboxylic acids. Four types of reactive intermediates arising from aldehydes and ketones during the deoxygenation, namely, bis‐electrophiles, carbenoids, bis‐nucleophiles and alkyl radical equivalents, are presented, while the carboxylic acids mainly behave as tris‐electrophiles when deoxygenated. In each subcategory, selected examples are organized according to the type of bond formation and discussed from a generalized mechanistic perspective. This Review recaps the development of selected deoxygenation methodologies for aldehydes, ketones and carboxylic acids, which take full advantage of the tremendous yet underexplored synthetic potential of carbonyl and carboxyl groups. Representative literature examples are discussed and their general features summarized, including characteristic reaction intermediates, typical reactivity patterns and commonly used conditions.